Empirical and analytical energy thresholds of Modulation-Coding Schemes research in IEEE 802.11η devices - Yu, Ilchenko M.; Uryvsky, L.; Moshynska, A.; Osypchuk, S. (2018 14th International Conference on Advanced Trends in Radioelecrtronics, Telecommunications and Computer Engineering (TCSET), 2018)
In modern IEEE 802.11 equipment the algorithms are implemented that control MCS (Modulation-Coding Schemes) selection depending on the statistical data of successfully transmitted and lost data packets, without taking into account the energy conditions in communication channel. In this paper, an applied experiment is performed in point-to-point (PtP) link with study the algorithm for MCS switching, with manual changing energy conditions in communication channel. As a result, empirical and analytical energy thresholds are analyzed to see how effective the implemented algorithm in IEEE 802.11 devices (Mikrotik) is.